Are global cities homogenizing? An assessment of urban form and heat island implications. (July 2022) - Stuhlmacher, Michelle; Georgescu, Matei; Turner, B.L.; Hu, Yi'na; Goldblatt, Ran; Gupta, Sarthak; Frazier, Amy E.; Kim, Yushim; Balling, Robert C.; Clinton, Nicholas
Abstract: The rapid growth of cities—along with the increasing connectedness of the world's social, economic, and political systems—has been hypothesized to generate a homogenization of urban form and associated environmental impacts. These hypotheses, however, have rarely been tested. Employing satellite imagery of 150 of the most populous cities in China, India, and the United States, we examine how the area and configuration of built-up land within cities has changed between 1995 and 2015 and assess impacts on the urban heat island effect. We find similar urban form trends across the three countries. The strongest evidence of homogenization is in the connectivity of urban form, while the shape of cities is linked to higher daytime surface urban heat island (SUHI) intensity. In the context of this and other research, we postulate that the identified urban form trends may lead to the homogenization of the biotic and abiotic environment of cities. Homogenization presents an opportunity for cities to learn from each other as they encounter similar ecological outcomes driven, in part, by their increasingly similar urban form. Highlights: Populous cities in China, India, and the U.S. have similar trends in urban form. Urban form exhibits a homogenizing trend for connectivity. Increasing shape compactness and complexity are linked with increasing SUHI intensity. If urban form homogenizes, cities can expect similar SUHI consequences.